Enhancing drought tolerance and Striga hermonthica resistance in maize using newly derived inbred lines from the wild maize relative, Zea diploperennis - Shaibu, A.S.; Badu-Apraku, Baffour; Ayo-Vaughan, M.A. (MDPI, 2021)
Recurrent drought and Striga hermonthica (Del.) Benth parasitism constrains maize production in sub-Saharan Africa (SSA). Transfer of resistance genes from wild relatives can improve resistance to drought and Striga in tropical maize. The objectives of this study were to (i) determine the combining ability of 12 extra-early yellow maize inbreds derived from Zea diploperennis and tropical maize germplasm; (ii) classify the inbreds into heterotic groups using heterotic grouping based on the general combining ability (GCA) of multiple traits (HGCAMT) method; (iii) examine hybrid performance under contrasting environments; and (iv) examine the stability of hybrid combinations involving the inbreds. Sixty-six diallel crosses involving the inbreds plus four checks were evaluated for two years under drought, Striga-infested and rainfed environments in Nigeria. Significant differences (p < 0.05) were observed for the effects of genotype, environment, genotype × environment, GCA and specific combining ability (SCA) on grain yield and other measured traits. Inbred lines such as TZdEEI 7 × TZEEI 63 derived from Z. diploperennis and tropical germplasm exceeded the checks by a range of 28 to 41%. Across environments, the hybrid TZdEEI 1 × TZdEEI 7, which was derived from Z. diploperennis, was the highest-yielding with a grain yield of 4302 kg ha−1. The results revealed the predominance of GCA over SCA effects for most measured traits, suggesting that additive gene action governed the inheritance of Striga resistance and drought tolerance related traits in the inbreds. The 12 inbreds were classified into three heterotic groups, while TZEEI 79 and TZdEEI 7 were identified as inbred testers and TZdEEI 7 × TZEEI 12 as a single-cross tester across environments. Hybrid TZdEEI 9 × TZEEI 79 was the highest-yielding and most stable. Other promising hybrids were TZdEEI 7 × TZEEI 79, TZdEEI 1 × TZdEEI 7 and TZdEEI 12 × TZEEI 95. These hybrids should be extensively tested on-farm for potential commercialization in SSA. Overall, our results highlighted the importance of harnessing beneficial alleles from wild relatives of maize for improvement of resistance to Striga and tolerance to drought in adapted maize germplasm.